2013
DOI: 10.11648/j.ijepe.20130202.13
|View full text |Cite
|
Sign up to set email alerts
|

Transformer Inrush Current Mitigation Using Controlled Switching and Magnetic Flux Shunts

Abstract: Abstract:The inrush current is a transient current that results from a sudden change in the exciting voltage across a transformer's windings. It may cause inadvertent operation of the protective relay system and necessitate strengthening of the transformer's mechanical structure. Many methods were reported in the literatures for reduction and mitigation of transformer inrush currents. This paper represents a study of techniques that have been proposed for transformer inrush current mitigation. A new, simple an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This technique is considered new in this field. There is also a simple technique based on the integration of a resistance in the neutral of the three-phase transformer, this technique is proposed in (Arand, 2013;Abdulsalam et al, 2017;Abdelsalam et al, 2015;Cui et al , 2005). This is not enough but the authors exploit the phase shift of the three phases to create a sequential excitation.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is considered new in this field. There is also a simple technique based on the integration of a resistance in the neutral of the three-phase transformer, this technique is proposed in (Arand, 2013;Abdulsalam et al, 2017;Abdelsalam et al, 2015;Cui et al , 2005). This is not enough but the authors exploit the phase shift of the three phases to create a sequential excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [8] presented a new approach where they modified the transformer coil distribution. Arand et al [9], Abdulsalam, and Xu [10], Abdelsalam and Abdelaziz [11] and Cui et al [12] suggested a simple technique by the insertion of a resistance between the neutral of the transformer and the ground, taking into account the sequential energization of the three phases. Using an existing photovoltaic generator.…”
Section: Introductionmentioning
confidence: 99%
“…A new approach was presented in Cheng et al based on changing the distribution of the coil windings to increase the transient inductance and hence limit the inrush current. Arand et al, Abdulsalam and Xu, Cui et al, and Xu et al proposed a simple method based on inserting a resistor in the neutral of the transformer, and with the sequential energization of each phase. Abdelsalam and Abdelaziz studied the reduction of the inrush current by the existing photovoltaic source; the reduction was achieved applying an opposite flux, taking into account the switching instant.…”
Section: Introductionmentioning
confidence: 99%